1987
DOI: 10.1210/mend-1-10-724
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Gonadotropin Subunit Messenger Ribonucleic Acids by Gonadotropin-Releasing Hormone Pulse Frequency in Ewes

Abstract: Changes in the frequency of GnRH and LH pulses have been shown to occur between the luteal and preovulatory periods in the ovine estrous cycle. We examined the effect of these different frequencies of GnRH pulses on pituitary concentrations of LH and FSH subunit mRNAs. Eighteen ovariectomized ewes were implanted with progesterone to eliminate endogenous GnRH release during the nonbreeding season. These animals then received 3 ng/kg body weight GnRH in frequencies of once every 4, 1, or 0.5 h for 4 days. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…However, subsequent analysis of the factors that were isolated in the screen demonstrated that none of the LIM-binding factors were dependent on NLI for binding. The bait and cDNA library plasmids were transformed into the L40 yeast strain (MATa his3⌬200 trp1-901 leu2-3, 112 ade2 LYS2:: (lexAop) 4 -His3 URA3::(lexAop) 8 -lacZ GAL4 gal80) (37) and selected for positive, interacting clones using histidine minus medium in the presence of 30 mM 3-aminotriazole to suppress the background activity of the bait. Further selection was performed on histidine minus medium containing 50 mM 3-aminotriazole.…”
Section: Methodsmentioning
confidence: 99%
“…However, subsequent analysis of the factors that were isolated in the screen demonstrated that none of the LIM-binding factors were dependent on NLI for binding. The bait and cDNA library plasmids were transformed into the L40 yeast strain (MATa his3⌬200 trp1-901 leu2-3, 112 ade2 LYS2:: (lexAop) 4 -His3 URA3::(lexAop) 8 -lacZ GAL4 gal80) (37) and selected for positive, interacting clones using histidine minus medium in the presence of 30 mM 3-aminotriazole to suppress the background activity of the bait. Further selection was performed on histidine minus medium containing 50 mM 3-aminotriazole.…”
Section: Methodsmentioning
confidence: 99%
“…Lesions of either the medial basal hypothalamus or the arcuate nucleus also eradicate LH pulses (1). By comparison, continuous infusion of LHRH, which desensitizes the gonadotropes through down-regulation of the LHRH receptor (14), also abolishes episodic secretion of LH and reduces LH 03-and a-subunit mRNA levels (15,16). While the relationship between LHRH and LH secretion is well established, it is unclear whether the generator for LHRH pulses is located within the LHRH neuronal network itself or within networks of other neighboring neurons or cells that directly affect LHRH secretion.…”
mentioning
confidence: 99%
“…[14] used the same animal model to demonstrate that the frequency of the pulsatile GnRH stimulus regulates LHp and a-subunit mRNA levels. In ovariectomized (OVX), progesterone-replaced sheep, the frequency of adminis tration of GnRH regulated mRNA levels of all three gonadotro pin subunits, with LHp and FSHp responding similarly, and a-subunit being regulated differently [24], Nilson et al [28] …”
mentioning
confidence: 99%